Analyses of suspended solid and nutrient loading in catchments with mixed landuse in Kranji, Singapore - Tan, Bee Ching (2009)
Urbanization has occurred in Singapore over the recent decades concurrent with the growth of Singapore’s population and economy. The process of urbanization has significantly impacted both the storm runoff volume and the timing and magnitude of the peak runoff rate. Urbanization also increases the variety and amount of pollutants transported to receiving waters, causing surface water quality deterioration. Studies on stormwater quantity and quality are hence vital for planning and managing water resources for catchments subjected to human perturbations. The objective of this study is to develop an approach for estimating long term runoffs and pollutant loadings for the Kranji catchment in Singapore, particularly as functions of land use.